Differences in soil bacterial community structure during the remediation of Cd-polluted cotton fields by biochar and biofertilizer in Xinjiang, China - Zhu, Yongqi; An, Mengjie; Anwar, Tumur; Wang, Haijiang (Frontiers in Microbiology, 2024)
Heavy metal pollution is a major worldwide environmental problem. Although many remediation techniques have been developed, these techniques have different performance in different environments. In this study, soil sampling was conducted in multiple cotton fields in Xinjiang, China, and found that cadmium (Cd) was the most abundant soil heavy metal. Then, to find the most suitable technique for the remediation of Cd pollution in cotton fields, a two-year study was conducted to explore the effects of cotton straw-derived biochar (BC, 3%) and Bacillus-based biofertilizer (BF, 1.5%) on cotton Cd uptake and transport and soil microbial community structure under Cd exposure conditions (soil Cd contents: 1, 2, and 4 mg•kg -1 ). The results showed that the bioaccumulation coefficients (Cd content of cotton organs / soil available Cd content) of cotton roots, stems, leaves, and buds/bolls reduced by 15.93%, 14.41%, 23.53%, and 20.68%, respectively after the application of BC, and reduced by 16.83%, 17.15%, 22.21%, and 26.25%, respectively after the application of BF, compared with the control (no BC and BF). Besides, the application of BC and BF reduced the transport of Cd from soil to root system, and enhanced the diversity of soil bacterial communities (dominant species: Alphaproteobacteria and Actinobacteria) and the metabolic functions related to amino acid synthesis. It was worth noting that the differential species for BF group vs BC group including Alphaproteobacteria, Gemmatimonadetes, Bacilli, and Vicinamibacteria were associated with the enrichment and transport of Cd, especially the transport of Cd from cotton roots to stems. Therefore, the application of BC and BF changed the soil bacterial diversity in Cd-polluted cotton field, and then promoted the transport of Cd in cotton, ultimately improving soil quality. This study will provide a reference for the selection of soil heavy metal pollution remediation techniques in Xinjiang, China.